EDUKASI PENINGKATAN PENGETAHUAN DAN PERILAKU KESELAMATAN KESEHATAN KERJA NELAYAN TERHADAP ALAT PELINDUNG DIRI - Fitri Sari Dewi (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Occupation, including fishermen, is one type of work that has potential hazards and risks of accidents and occupational diseases because fishing activities are carried out in the middle of the sea or along the coast. Fishermen can experience work accidents such as drowning, drifting, ship damage, injuries due to fish spines, low back pain, fever and others. Fishermen need personal protective equipment to reduce the risk of accidents and occupational diseases. The objectives of holding education to increase knowledge and behavior of fishermen's occupational health safety regarding personal protective equipment in fishermen settlements in Galang District, Batam City are: 1) increasing knowledge of occupational safety and health of fishermen regarding fishermen's personal protective equipment. 2) improve fishermen's occupational safety and health behavior towards personal protective equipment. 3) fishermen can use standard personal protective equipment.